Effect of Tiotropium on Post Pulmonary TB Patients With Obstructive Abnormalities to Lung Function and Quality of Life - Romaito Nasution; Irvan Medison; Deddy Herman; Masrul Basyar (Jurnal Respirologi Indonesia, 2018)
Background: Post pulmonary tuberculosis (TB) patients could experience pulmonary function declines which affected their quality of life. Obstrucitve abnormalities were found the most after complete TB treatment and the therapeutic guidelines focused in bronchodilators. The use of bronchodilators could improve lung function and quality of life in post TB patients with obstructive abnormalities. Tiotropium is a bronchodilator that has been shown to be effective in chronic obstructive pulmonary disease (COPD) patients, while its use in post TB patients has not been widely studied. Methods: This study design was a clinical trial with pre and post test design in post TB patients in Dr.M.Djamil Padang General Hospital and Lubuk Alung Pulmonary Hospital conducted from November 2016 to June 2017. Results: Of 30 post TB patients, the mean age was 62.77±10.99 years, most were male (63.33%), non-smokers and former smokers (50% each), had interval from complete anti TB drugs to study ≥6 months (53.3%), and moderate level of obstruction (80%). Pulmonary function prior to tiotropium was generally in moderate obstruction (FEV1 68,85±15,77). The mean quality of life prior to tiotropium was 18.27±10.81. There was no improvement in pulmonary function of post TB patients after administration of tiotropium, P=0.920, however, there was an improvement in the quality of life, P=0.009. No adverse events were found in this study. Conclusions: Administration of 2 months tiotropium in post TB patients had no effects on the improvements of lung function but improved the quality of life. More studies were needed using more patients and longer duration of administration. (J Respir Indo. 2018; 38: 203-9)